Misconceptions of science learning on force and motion material for elementary school - Maryani, Widi Ika; Atmojo, Idam Ragil Widianto (Jurnal Ilmiah Pendidikan Dasar, 2024)
One of the factors contributing to the low learning outcomes of physics students in school is the lack of concept mastery. The aim of carrying out this research is to provide insight to educators regarding identifying misconceptions about force and movement and to assist teachers in resolving these misconceptions. The research method uses a narrative literature review. The data obtained were 20 national and international journal articles randomly indexed by Sinta and Scopus regarding the concept of science learning on force and motion material in elementary education in 2012 - 2024. Data collection techniques were carried out through literature studies. Data analysis techniques from this research consist of research questions, conducting searches, identifying keywords, reviewing abstracts and articles, and resulting documents. The findings of this research show that there are still misconceptions in science learning regarding friction force, gravitational force, and free-fall motion. This misconception occurs among pupils and students (prospective teachers). The causes of these misconceptions are the students themselves, teaching materials, context, teachers, and teaching methods. The implication of this research provides an illustration that teachers must use interactive, innovative, and creative media with innovative learning models to minimize students' misconceptions in elementary schools so that learning is appropriate to students' cognitive development stages, namely concrete operations.